2019
DOI: 10.1111/jjns.12279
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural adaptation of the Chronic Illness Resources Survey in Japanese patients with diabetes

Abstract: Aim: The Chronic Illness Resources Survey (CIRS) is a tool for assessing multiple levels of resources for self-management in people with chronic illnesses. This study aimed to examine the reliability and validity of the Japanese version of the CIRS (CIRS-J) among patients with diabetes. Methods: This study included 102 Japanese patients with diabetes. Patients completed the CIRS-J on two occasions with additional measurements, including the multidimensional scale of perceived social support (MSPSS), the summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…( 2016 ) indicated that support of emotional support and information from media promoted patients activation. Support from social resources positively influence patients’ attitude and the physical activity levels (Sato et al., 2020 ). A systematic review summarized that patient activation was an effect intervention on improving self‐management behaviours in diabetes patients (Almutairi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2016 ) indicated that support of emotional support and information from media promoted patients activation. Support from social resources positively influence patients’ attitude and the physical activity levels (Sato et al., 2020 ). A systematic review summarized that patient activation was an effect intervention on improving self‐management behaviours in diabetes patients (Almutairi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently research shows that social aspects (support from family, friends and healthcare etc.) are significant for promoting self-management behaviours; furthermore, it highlighted the positive relationship between chronic illness resources and self-management behaviours (Sato et al, 2020). Witt et al (2016) indicated that support of emotional support and information from media promoted patients activation.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the positive association between social-ecological support and self-management behaviors. [39] Moreover, the act of sharing thoughts and feelings with healthcare professionals or others is shown to mitigate negative emotions and contribute to improved emotional adjustment for T2DM. [40] Chronic illness resources, encompassing various tools for self-management in individuals with chronic conditions, serve to alleviate diabetes-related distress and sustain effective self-management behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…CIRS derived from the pyramid model overcomes the disadvantage of the previous assessment tools which were limited to a certain area of resource support. Recent studies showed that CIRS has been successfully applied to diabetes education programs abroad (Eakin et al., 2007 ; Sato et al., 2020 ); however, CIRS has not been used in China for diabetic foot patients, so the relationship between RHD and the utilization of available chronic illness resources is not clear at the present time. Given the limited research conducted in diabetic foot patients, more evidence is needed to understand the experiences of these patients and find an effective approach to improve discharge planning.…”
Section: Introductionmentioning
confidence: 99%